2017
DOI: 10.1039/c6ra26567g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure–activity relationship studies of teixobactin analogues

Abstract: A new series of teixobactin analogues were prepared using a convenient synthetic strategy and their antibacterial activities were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 19 publications
2
80
0
Order By: Relevance
“…Although the removal of the N ‐methyl group from N ‐Me‐ d ‐Phe 1 has a minimal effect on the potency, activity was lost when Wu et al. replaced d ‐Phe with d ‐Tyr . The same observation was obtained with analogue 69 , in which the phenyl group was substituted with an indole moiety; our ( d ‐Trp 1 ,Arg 10 ) analogue 69 is essentially inactive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the removal of the N ‐methyl group from N ‐Me‐ d ‐Phe 1 has a minimal effect on the potency, activity was lost when Wu et al. replaced d ‐Phe with d ‐Tyr . The same observation was obtained with analogue 69 , in which the phenyl group was substituted with an indole moiety; our ( d ‐Trp 1 ,Arg 10 ) analogue 69 is essentially inactive.…”
Section: Resultsmentioning
confidence: 99%
“…Teixobactin ( 1 ), comprised of a 13‐membered depsipeptide core and a tethered linear heptapeptide, offers multiple sites for synthetic modifications to improve its potency and efficacy. In less than three years since its discovery, more than a hundred analogues have been synthesised by various research groups in the hope of elucidating its structure–activity relationships (SARs) . The biological activities of these analogues and the different synthetic strategies reported have been comprehensively reviewed .…”
Section: Introductionmentioning
confidence: 99%
“…4 Several research groups have substituted this amino acid with commercially available building blocks such as Arginine, 6 7 Lysine 8 or Histidine. 12 The obtained analogues were less active than the natural product. However, the biological activity of teixobactin analogues suggests they are still suitable for further development as potential antibacterials.…”
Section: Syntheses Of Potent Teixobactin Analogues Against Methicillimentioning
confidence: 99%
“…reported that Lys10/Arg10, Ser7 and the NH-group of the N terminal phenylalanine are critical for the biological activity of teixobactin analogues. 12 Replacement of Arg10 or Lys10 by His10, Ser7 by Ala7 and N-Methyl phenylalanine1 by N, N-dimethyl phenylalanine1 leads to less active teixobactin analogues compared to Arg10-teixobactin. During the preparation of this manuscript, a series of teixobactin analogues using convergent Ser/Thr ligation was published by Li et.…”
Section: Syntheses Of Potent Teixobactin Analogues Against Methicillimentioning
confidence: 99%
“…1) and related homologues in which arginine is used as a surrogate for allo -enduracididine. 813 Very recently, Singh et al reported NMR-based structures and structure-activity-relationships of Arg 10 -teixobactin and its diastereomers at positions 1, 4, 5, and 8. 14 …”
mentioning
confidence: 99%